Motivasi Manajer dalam Melakukan Manajemen Laba Dikaji dalam Pandangan Islam - Ilhamda Azis (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2020)
Managers’ motivation to do earnings management are due to the capital market expectations, management compensation contracts, lending contracts motivations, political motivation. This study aimed to review managers’ movitation in earnings management viewed from Islamic perspective that sourced from the Qur'an and Hadith, as well as supplemented by PSAK Sharia. The results of the study stated that manager's motivation for earnings management is still within the limits of accounting standards. Compliance in application of accounting standards is reflected by the obligation to obey Ulil Amri. However, utilizing position to maximize bonuses, presenting biased information, presenting lust are attitudes that is prohibited in Islamic teachings. Abstrak Motivasi manajer dalam manajemen laba adalah berupa capital market expectations, management compensation contract, lending contracts motivations, dan political motivation. Penelitian ini bertujuan untuk mengkaji motivasi manajer dalam manajemen laba dilihat dari perspektif Islam yang bersumber dari Alquran dan Hadis, serta dilengkapi oleh PSAK Syariah. Hasil studi menyatakan motivasi manajer untuk melakukan manajemen laba masih dalam batasan standard akuntansi. Kepatuhan dalam penerapan standar akuntansi merupakan cerminan kewajiban taat kepada ulil amri. Akan tetapi, memanfaatkan jabatan untuk memaksimalkan bonus, penyajian informasi bias, memperturutkan hawa nafsu merupakan sikap yang dilarang dalam ajaran Islam.